2004
DOI: 10.1016/j.topol.2003.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Embeddings into pseudocompact spaces of countable tightness

Abstract: The finite derived set property asserts that any infinite subset of a space has an infinite subset with only finitely many accumulation points. Among other things, we study this property in the case of a function space with the topology of pointwise convergence.2000 AMS Classification: 54A25, 54A35, 54D55.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The idea to use parametrization by ordinal pairs in order to get countable tightness was first suggested by O. Pavlov in the attempt to find a pseudocompact Tychonoff countably tight space without countable fan tightness. This and other results can be found in [4].…”
Section: So We May Suppose Thatsupporting
confidence: 85%
“…The idea to use parametrization by ordinal pairs in order to get countable tightness was first suggested by O. Pavlov in the attempt to find a pseudocompact Tychonoff countably tight space without countable fan tightness. This and other results can be found in [4].…”
Section: So We May Suppose Thatsupporting
confidence: 85%
“…Simon first studied these spaces in [62] (using different terminology) and showed that there are two Whyburn spaces whose product is not weakly Whyburn. In [90], assuming CH, Bella and Simon construct a pseudocompact Whyburn space of countable tightness that is not Fréchet.…”
Section: Convergence Propertiesmentioning
confidence: 99%
“…Moving from countably compact to pseudocompact appears much harder. Indeed, with a lot of effort, Bella and Pavlov [20] constructed a Tychonoff pseudocompact space of countable tightness which does not have countable fan tightness. But such a space has a countable set of isolated points and so it is selectively separable.…”
Section: So We Getmentioning
confidence: 99%